2014
DOI: 10.1002/hon.2127
|View full text |Cite
|
Sign up to set email alerts
|

Can flow cytometry of bone marrow aspirate predict outcome of patients with diffuse large B cell lymphoma? A retrospective single centre study

Abstract: Bone marrow (BM) trephine biopsy is a part of routine staging of patients with newly diagnosed diffuse large B cell lymphoma (DLBCL). The significance of lymphoid monoclonal population on flow cytometry (FC) of the BM aspirate in the presence of negative BM histology has not been clarified. In this study, we assessed the clinical role of positive FC in predicting outcome of patients with DLBCL and a negative BM histology. We retrospectively analysed 101 patients diagnosed with DLBCL at a single institution bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Based on this finding, we speculate the complementary role between the two modalities. Although the prognostic association between BM involvement detection by biopsy and FCM has been controversial [ 18 , 19 , 20 , 27 ], our result indicated the combination of BM biopsy and FCM as the central component in BM analysis. BM smear and clot examinations are also useful modalities, as they may provide additional information and play the alternative role in some clinical situations.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on this finding, we speculate the complementary role between the two modalities. Although the prognostic association between BM involvement detection by biopsy and FCM has been controversial [ 18 , 19 , 20 , 27 ], our result indicated the combination of BM biopsy and FCM as the central component in BM analysis. BM smear and clot examinations are also useful modalities, as they may provide additional information and play the alternative role in some clinical situations.…”
Section: Discussionmentioning
confidence: 66%
“…Antigens examined included CD2, CD3, CD4, CD7, CD8, CD10, CD11c, CD16, CD19, CD20, CD23, CD25, CD34, CD45, CD56, kappa light chain, and lambda light chain. The presence of light chain restriction in B lymphoid cells was regarded as positive BM invasion [ 15 , 16 , 17 , 18 , 19 , 20 ]. BM aspirate smear specimen was subjected to Wright–Giemsa staining and 500 BM nucleated cells were cytologically evaluated to detect abnormal lymphoid cells under an optical microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies [43,49] that analyzed outcomes after combining BMB/FCM findings described discrepancies about the worse prognosis of BMB+/FCM+ cases compared with BMB−/FCM+ ones. On the one hand, M. Moro et al reported that the BMB−/FCM+ group presented an adverse outcome equivalent to the BMB+/FCM+ population; similar findings were described in another study not included in the comparative review due to insufficient data [56]. On the other hand, Greenbaum et al described that the prognosis of BMB−/FCM+ cases was intermediate between the BMB−/FCM− and the BMB+/FCM+ groups.…”
Section: Outcomes According To Bmi By Bmb and Fcm In Newly Diagnosed ...mentioning
confidence: 60%
“…The World Health Organization (WHO) classification of mature B-cell leukaemia/lymphoma, as in other hematological malignancies, morphology, immunophenotypic characteristics, genetic and clinical findings are used (1). Immunophenotypic classification plays an important role in determining the cell origin of mature B-cell leukemia/lymphoma, as well as in patient management and follow-up, and is a sensitive method (2). Immunophenotyping is performed by immunohistochemical (IHC) studies in bone marrow biopsies and with by flow cytometry (FC) in bone marrow aspirate suspensions (1).…”
Section: Introductionmentioning
confidence: 99%